Hydrogenation/oxidation induced efficient reversible color switching between methylene blue and leuco-methylene blue. Issue 48 (9th June 2017) - Liu, Ya-Nan; Zhou, Xiao; Wang, Xin; Liang, Kuang; Yang, Zheng-Kun; Shen, Cong-Cong; Imran, M.; Sahar, Shafaq; Xu, An-Wu
Abstract : A novel reversible color switching system based on one-pot hydrogenation/oxygenation reactions, and with excellent cycling performance and high switching rates as an oxygen indicator. Abstract : In this paper, we present the use of graphitic carbon nitride (g-C3 N4 ) supported palladium nanoparticles (Pd/g-C3 N4 ) for reversible color switching of methylene blue (MB). g-C3 N4 with a high polymeric degree could improve the dispersity of Pd nanoparticles, contributing to fast color switching of MB as the agglomeration of metal nanoparticles is significantly prevented. Moreover, strong metal-support interaction (SMSI) between Pd nanoparticles and g-C3 N4 support promotes the adsorption and subsequent dissociation of molecular hydrogen and oxygen, thus leading to efficient reversible conversion between MB and leuco-methylene blue (LMB). Our obtained Pd/g-C3 N4 nanocatalyst exhibits outstanding hydrogenation activity of blue MB to colorless LMB with a turnover frequency as high as 165 h −1 at room temperature, moreover, colorless LMB can quickly switch back to MB upon exposing the same reaction system to oxygen for oxidation. It is noted that our color switching system exhibits remarkable reversibility and stability without obvious fatigue even after 10 consecutive cycles. This novel redox-driven reversible color switching system could find potential in food packaging, sensing and organic transformations.